Total dan Diferensial Leukosit Ayam Petelur Pascavaksinasi Tetelo dan Flu Burung (TOTAL AND DIFFERENTIAL LEUKOCYTES OF LAYER AFTER NEWCASTLE DISEASE AND AVIAN INFLUENZA VACCINATION) - Kencana, Gusti Ayu Yuniati; Kendran, Anak Agung Sagung; Anggreni, Luh Dewi; Widyasanti, Ni Wayan Helpina (Jurnal Veteriner; Vol 19 No 2 (2018)DO - 10.19087/jveteriner.2018.19.2.190, 2018)
The purpose of this study was to determine total and differential leukocyte of layer after vaccinated with Newcastle Disease (ND) and Avian Influenza (AI) combination vaccine. The research was conducted on commercial layer breeding in Denbatas Village, Tabanan Sub-district, Bali. This study used 30 layer samples. Vaccination was done with ND-AI combination vaccine which was a combination of ND vaccine strain Lasota with AI vaccine subtype H5N1. ND-AI combination vaccine was an inactive vaccine. Chicken was vaccinated at 18 weeks of age before laying eggs. Vaccination was done with one dose (0.5 ml) through thigh muscle injection. Chicken blood sampling was done twice ie, two weeks and three weeks after vaccination. The examination of the total leukocytes was performed by count chamber, whereas the differential leukocyte was examined from a blood smear preparation by Giemsa staining. Data of total and differential leukocyte examination were analyzed by descriptively quantitative. The results concluded that layer has leukopenia and heteropenia which were probably caused by hormonal factors and stress due to blood collection.